Putative neurochemical and cell type contributions to hemodynamic activity in the rodent caudate putamen. Issue 4 (April 2023) - Katz, Brittany M; Walton, Lindsay R; Houston, Kaiulani M; Cerri, Domenic H; Shih, Yen-Yu Ian
Functional magnetic resonance imaging (fMRI) is widely used by researchers to noninvasively monitor brain-wide activity. The traditional assumption of a uniform relationship between neuronal and hemodynamic activity throughout the brain has been increasingly challenged. This relationship is now believed to be impacted by heterogeneously distributed cell types and neurochemical signaling. To date, most cell-type- and neurotransmitter-specific influences on hemodynamics have been examined within the cortex and hippocampus of rodent models, where glutamatergic signaling is prominent. However, neurochemical influences on hemodynamics are relatively unknown in largely GABAergic brain regions such as the rodent caudate putamen (CPu). Given the extensive contribution of CPu function and dysfunction to behavior, and the increasing focus on this region in fMRI studies, improved understanding of CPu hemodynamics could have broad impacts. Here we discuss existing findings on neurochemical contributions to hemodynamics as they may relate to the CPu with special consideration for how these contributions could originate from various cell types and circuits. We hope this review can help inform the direction of future studies as well as interpretation of fMRI findings in the CPu.